2011
DOI: 10.1007/s00464-011-1611-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving functional esophageal surgery with a “smart” bougie: endoflip

Abstract: The endoflip provides a system in which physiology and anatomy are represented dynamically in the same image. This "smart bougie" could be integrated into the surgical routine to improve outcome and to facilitate surgical training and the learning curve in esophageal functional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…As patients with fundoplication appear to have reduced EGJ distensibility compared with controls, 4 FLIP may be a useful tool to aid anti-reflux procedures (such as fundoplication) 24 . Several studies demonstrated the feasibility of intra-operative FLIP use during fundoplication and a consistent reduction in EGJ-distensibility immediately following fundoplication 24, 25 .…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…As patients with fundoplication appear to have reduced EGJ distensibility compared with controls, 4 FLIP may be a useful tool to aid anti-reflux procedures (such as fundoplication) 24 . Several studies demonstrated the feasibility of intra-operative FLIP use during fundoplication and a consistent reduction in EGJ-distensibility immediately following fundoplication 24, 25 .…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…Median Eckardt score before POEM was 8 (range [5][6][7][8][9][10][11][12]. Thirteen patients had a type I achalasia at high-resolution manometry; 10 a type-II.…”
Section: Resultsmentioning
confidence: 99%
“…The first suggested intraoperative use of the FLIP for surgery was by Perretta et al [52]. A more recent study has indicated that intraoperative measurement of the distensibility of the EGJ using the FLIP can predict the clinical outcome of Heller myotomy and POEM [51].…”
Section: Achalasiamentioning
confidence: 99%